2021
DOI: 10.1055/a-1652-1351
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as a Source of Patient Information on Myofascial Pain Syndrome

Abstract: Introduction Myofascial pain syndrome is a local disorder characterised by pathological myofascial constrictions and trigger points. One of the most popular sources of internet-based information for patients is YouTube, which provides a lot of videos related to myofascial pain syndrome, making it one of the top clinical conditions searched for on the site. This study aimed to examine the quality of the YouTube v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…As well as choosing the videos by patients that they can really benefit is essential, it is thought that the most-watched, liked, commented and popular videos may not really inform the patients meticulously and precisely. In parallel, a study by Şan [22] about YouTube videos of myofascial syndrome showed that the VPI scores, video likes and video views were highest in the intermediate group; on the contrary number of video likes and number of video views were the lowest in the high-quality group. These findings emphasize that the most popular videos on the internet may not always include the highest quality information [22].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As well as choosing the videos by patients that they can really benefit is essential, it is thought that the most-watched, liked, commented and popular videos may not really inform the patients meticulously and precisely. In parallel, a study by Şan [22] about YouTube videos of myofascial syndrome showed that the VPI scores, video likes and video views were highest in the intermediate group; on the contrary number of video likes and number of video views were the lowest in the high-quality group. These findings emphasize that the most popular videos on the internet may not always include the highest quality information [22].…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, a study by Şan [22] about YouTube videos of myofascial syndrome showed that the VPI scores, video likes and video views were highest in the intermediate group; on the contrary number of video likes and number of video views were the lowest in the high-quality group. These findings emphasize that the most popular videos on the internet may not always include the highest quality information [22]. In another study by Kocyigit et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations